Identificación de mercados potenciales para la exportación de la cerveza artesanal (2021)
In this work, the ultimate goal is a potential market for the export of craft beer. In Colombia year after year, the distribution of craft beer has been stronger, with a percentage growth of 30%. Where several craft brewing festivals have been highlighted in Colombia where national and international brands participate.